Assessment of sleep quality, daytime sleepiness, and sleep hygiene practices among adults in a metropolitan city: a cross-sectional study - Sharma, Sakshi; Chatterjee, Kunal; Rath, T. K.; Mahajan, Saurabh; Samanta, Indranil; Misra, Akshay; Kaul, Somesh M. (International Journal Of Community Medicine And Public Health, 2025)
Background: Adequate sleep is crucial for cognitive function, workplace performance, and mental health in adults. However, various factors, including workplace pressure, technology use, and sociocultural norms, can significantly impact sleep patterns, particularly in urban settings. This cross-sectional study assessed sleep quality, daytime sleepiness prevalence, and sleep hygiene practices among adults in an urban community in Delhi (Northern India), and the factors associated with these sleep parameters in this understudied population. Methods: A cross-sectional study was conducted among 384 adults who were assessed using a self-reported proforma of sociodemographic details, behavioral factors, Pittsburgh Sleep Quality Index (PSQI), Epworth Sleepiness Scale (ESS), and Sleep Hygiene questionnaire. Results: Of the 384 participants, 72.1% (277 out of 384 participants) were classified as having poor sleep quality (PSQI ≥5), and 29.4% reported excessive daytime sleepiness (ESS ≥10). Poor sleep hygiene behaviors were notably prevalent, with 65.1% of adults reporting reading in bed, 54.7% watching television in bed, and 46.9% eating in bed. Conclusions: This study highlights the significant prevalence of poor sleep quality and excessive daytime sleepiness among adults in an urban community in Northern India. Factors such as irregular sleep-wake schedules, screen use before bedtime, internet addiction and high workloads adversely affect sleep health.